2006
DOI: 10.1128/jcm.01181-06
|View full text |Cite
|
Sign up to set email alerts
|

Beijing Genotype of Mycobacterium tuberculosis Is Significantly Associated with Human Immunodeficiency Virus Infection and Multidrug Resistance in Cases of Tuberculous Meningitis

Abstract: Multidrug-resistant tuberculous meningitis is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 25 publications
4
47
0
1
Order By: Relevance
“…Multidrug resistance is a strong independent risk factor for a poor outcome for all forms of tuberculosis (21) and, when strongly linked to mycobacterial genotype, provides a clinically important influence of the bacterial genotype on the outcome. We recently reported a strong association between the Beijing genotype and drug resistance for HIV-infected Vietnamese adults with tuberculous meningitis (5). This study suggests the relationship holds for HIV-uninfected adults with pulmonary disease, and similar findings have been reported from Russia (9) and Kazakhstan (15).…”
Section: Discussionsupporting
confidence: 71%
“…Multidrug resistance is a strong independent risk factor for a poor outcome for all forms of tuberculosis (21) and, when strongly linked to mycobacterial genotype, provides a clinically important influence of the bacterial genotype on the outcome. We recently reported a strong association between the Beijing genotype and drug resistance for HIV-infected Vietnamese adults with tuberculous meningitis (5). This study suggests the relationship holds for HIV-uninfected adults with pulmonary disease, and similar findings have been reported from Russia (9) and Kazakhstan (15).…”
Section: Discussionsupporting
confidence: 71%
“…Previous studies have reported that TB caused by the Beijing lineage was associated with multidrug resistance, coinfection with HIV, homelessness, and institutional (e.g., hospital or prison) transmission (11,17,32). To evaluate for Rio patient strain numbers are lightly shaded and boxed; WT LAM patient strain numbers have dark shading; and WT non-LAM patient strain numbers are neither shaded nor boxed.…”
Section: Mtc Pcr Typing Panel Resultsmentioning
confidence: 99%
“…Within the east Asian lineage, the Beijing genotype has been extensively investigated, as it is widespread and associated with increased virulence. It shows significant association with HIV status, single-and multi-drug resistance [42]. Patients infected with Beijing strain had shorter duration of illness before presentation to hospital and fewer CSF leukocytes, suggesting that mycobacterial genotype may affect disease progression and the intracerebral inflammatory response [43].…”
Section: Immunologymentioning
confidence: 99%